The Relationship Between Sleep Quality and Stress Level in Biology Education Students - Wijayanti, Erna; Eka Yuliani, Apreza; Bulut, Sefa (Indonesian Journal of Science and Education, 2025)
Sleep is a fundamental physiological process essential for maintaining mental and physical health. University students, particularly those in demanding academic programs, often experience sleep disturbances that may influence their stress levels. This study aimed to determine the relationship between sleep quality and stress levels among Biology Education students at UIN Walisongo Semarang. A descriptive–analytic study with a cross-sectional design was conducted involving 36 students selected through proportional random sampling from the 2020–2022 cohorts. Sleep quality was measured using the Pittsburgh Sleep Quality Index (PSQI), while stress levels were assessed using the Perceived Stress Scale (PSS). Data were analyzed using the Chi-square test at a 95% confidence level (α = 0.05). The findings indicated that most respondents (97.2%) experienced poor sleep quality and moderate stress levels (86.1%). Statistical analysis showed no significant relationship between sleep quality and stress levels (χ² = 0.165, p = 0.920). Although most students experienced poor sleep quality and moderate stress, no significant association was found between these two variables. Further research with a larger and more diverse sample is recommended to confirm these findings and explore additional factors affecting students’ sleep and stress patterns.